2001
DOI: 10.1078/0944-5013-00098
|View full text |Cite
|
Sign up to set email alerts
|

Screening for trbB- and traG-like sequences by PCR for the detection of conjugative plasmids in bacterial soil isolates

Abstract: The transfer regions of different conjugative plasmids show significant similarities in the genetic organization and in the amino acid sequence of some gene products, especially of proteins from the traG or trbB family. These similarities are also evident on the level of the nucleotide sequences. On the basis of conserved DNA regions we designed degenerate PCR primer pairs to detect specifically tra regions within a collection of bacterial clones isolated from an agricultural soil. Most of the potential transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Many DNA sequences are now available for Bacillus replicons and transfer region, facilitating the development of a series of oligonucleotide primers for use in PCR to permit the assessment of the distribution and diversity of replication and transfer functions in Bacillus isolates from natural environments and enable investigation of the linkage of such elements. Such approaches have been utilised successfully in the study of plasmids from Gram-negative bacteria, for example for a series of broad host range plasmids [6], and more recently to study IncN-related plasmid replicons [7] and conjugative plasmid transfer regions [8].…”
Section: Introductionmentioning
confidence: 99%
“…Many DNA sequences are now available for Bacillus replicons and transfer region, facilitating the development of a series of oligonucleotide primers for use in PCR to permit the assessment of the distribution and diversity of replication and transfer functions in Bacillus isolates from natural environments and enable investigation of the linkage of such elements. Such approaches have been utilised successfully in the study of plasmids from Gram-negative bacteria, for example for a series of broad host range plasmids [6], and more recently to study IncN-related plasmid replicons [7] and conjugative plasmid transfer regions [8].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in Chryseomonas luteola IU-7, the visible plasmids were smaller than the 30 kb needed for encoding the conjugative function (Rochelle et al, 1989). In this strain, plasmids with the conjugative function may be present on non-visible plasmids or megaplasmids (Disqué-Kochem et al, 2001), which are difficult to detect by the method employed in this study.…”
mentioning
confidence: 58%
“…Recently, Disqué-Kochem et al (2001) designed universal PCR primers to detect the traG-and trbB-like genes in the tra region, and demonstrated that they could detect bacteria with plasmids capable of mobilizing a Tra Ϫ plasmid from an agricultural soil sample.…”
mentioning
confidence: 99%
See 2 more Smart Citations